Asymmetry in contralateral muscle excitation in proximal vs. distal muscles in upper extremities - Nynes, Alexander; McGhie, David; Aune, Morten Andreas; Aune, Tore Kristian (Frontiers in Psychology, 2025)
IntroductionThe purpose of the study was to investigate potential asymmetry in contralateral muscle excitation (CME) in proximal versus distal muscles. Given the dominant arm’s greater accuracy in unilateral tasks, reinforced by habitual use and neural specialization, along with neurophysiological constraints in the central nervous system and functional differences between proximal and distal muscles, higher CME was hypothesized in both the dominant compared to non-dominant and proximal compared to versus distal muscles. Secondly, a proximal-distal gradient of asymmetry in CME was hypothesized, with more pronounced bilateral asymmetry for distal compared to proximal muscles.MethodsIsometric shoulder and index finger flexion on the dominant and non-dominant arm was performed at 25, 50, 75, and 100% of maximum isometric force. Muscle excitation was measured using sEMG placed on the non-active contralateral flexor carpi radialis (FCR; distal condition) and on the anterior deltoid (proximal condition) on both the dominant and non-dominant arm.ResultsIn the unilateral shoulder flexion (proximal condition), no CME asymmetry between the non-active anterior deltoid on the dominant and non-dominant arm was observed. In contrast, in unilateral index finger flexion (distal condition), a pronounced asymmetry in CME was observed, with the FCR on the dominant arm exhibiting greater CME compared to the FCR on the non-dominant arm.DiscussionThese findings highlight neurophysiological distinctions of the dominant side, especially in distal muscles where refined neural circuits support greater CME. In contrast, the absence of asymmetry in proximal muscles is consistent with their stronger bilateral communication, facilitated by denser interhemispheric and spinal commissural pathways. Overall, the results indicate that CME asymmetries are shaped by both cortical specialization and structural differences in neural connectivity, offering new insight into how dominance and proximal–distal distinctions interact in motor control.